"Inclusion is definitely a possibility for all": Promoting inclusive education through a critical professional development schools model - Latifa Sebti; Brent C. Elder (Emerald Publishing, 2024)
Purpose - In this article, we highlight ways in which disability critical race theory (DisCrit) (Annamma et al., 2013), inclusive education and community-based participatory research (CBPR) can be used within professional development schools (PDS) to provide students with disabilities with more access to inclusive classrooms. At a grade 4-6 elementary school, we developed a model of a critical PDS to promote inclusive education and facilitate the transition of students of color with disabilities from self-contained to inclusive classrooms. We conducted semi-structured interviews and used action plan meetings with school administrators, teachers, professionals and students with disabilities and their parents to assess the impact of our critical PDS model. Findings suggest this model had a positive impact on administrators' and teachers' critical consciousness, ideological and instructional practices, students of color with disabilities' social, academic and personal outcomes, as well as a schoolwide culture of inclusion and social justice. This study can inform tailored professional development efforts to improve educators' inclusive practices. Design/methodology/approach - We conducted semi-structured interviews and used action plan meetings with school administrators, teachers, professionals and students with disabilities and their parents to assess the impact of our critical PDS model. Findings - The findings of this study suggest this model had a positive impact on administrators' and teachers' critical consciousness, ideological and instructional practices, students of color with disabilities' social, academic and personal outcomes, as well as a schoolwide culture of inclusion and social justice. Practical implications - This study can inform tailored professional development efforts aiming to improve educators' inclusive practices. Originality/value - We developed a model of a critical PDS to promote inclusive education and facilitate the transition of students of color with disabilities from self-contained to inclusive classrooms.